Simulation of Solar Photovoltaic System and Grid Integration - Patel, Brijeshkumar J; Chauhan, Manishkumar. J (International Journal of Computer Sciences and Engineering, 2019)
This paper focuses on the study of grid connected solar photovoltaic energy conversion system modeling and control in MATLAB Software. In the modeling part photovoltaic systems have SPV array, boost converter, MPPT technique, inverter, filter and transformer. It also shows the detailed representation of the main components of the SPV system. The PV system performance mainly varies as per the location, surrounding condition, temperature and irradiation. That’s why prediction of irradiation is very important for the generation. There is lot of scope for the researchers in Maximum Power Point Tracking technique and how-to make it more efficient by increasing the tracking speed and accuracy for maximum power output from SPV system. The MPPT technique explained in this paper is Incremental Conductance based on hill climbing method which helps to extract maximum power from the SPV system. This paper will help the researchers to understand the method available for grid integration of solar photovoltaic system as well as to model and control such system for better results.